IDENTIFICATION AND MOLECULAR CHARACTERIZATION OF BACTERIA HAVING ANTIMICROBIAL AND ANTIBIOFILM ACTIVITY - Sharma, Garima; Dang, Shweta; Gupta, Sanjay; Gabrani, Reema (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The aim of the current study was to isolate and identify the bacteriocinogenic strain exhibiting broad range antimicrobial activity and antibiofilm activity from soil of animal farms. Methods: In the current study, bacterial strains were isolated from soil of twelve different regions of animal farm all over India and screened for antimicrobial activity against Staphylococcus epidermidis, Micrococcus luteus, Pseudomonas fluorescence and Escherichia coli. Antibiofilm ability of these selected strains was checked on preformed biofilm of S. epidermidis and in addition biofilm disruption potential was also determined. The potent bacterial strain was identified at molecular level by 16S ribosomal DNA (rDNA) sequencing. Results: 30 out of 231 strains isolated from soil were selected on the basis of antibacterial activity against S. epidermidis. One potential candidate (GAS 101) exhibited â‰¥99% inhibition against S. epidermidis, M. luteus, P. fluorescence and E. coli and also showed antibiofilm activity. GAS 101 16S rDNA sequencing data identified it as Bacillus subtilis. The sequence of B. subtilis was submitted to genbank under accession no. KJ564301. Conclusion: B. subtilis GAS 101 isolated from soil of animal farm showed the antibacterial activity against all indicator organisms and also displayed antibiofilm activity against preformed biofilm and inhibited biofilm formation of S. epidermidis.